(x²y²-2xy+1)+(x²-2xy+y²)=0 (xy-1)²+(x-y)²=0 平方大于等于0,相加等于0,若有一个大于0,则另一个小于0,不成立.所以两个都等于0 所以xy=1,x-y=0 所以x=y=1或x=y=-1 所以x+y=2或x+y=-2
x平方y平方-4xy+x平方+y平方+1=0 ,则x+y=( )
1个回答
相关问题
-
若x平方+xy-2y平方=0,则(x平方+3xy+y平方)除以(x平方+y平方)=?
-
已知x平方+xy=1,xy-y平方=-3.则x平方+y平方=( ).x平方+2xy-y平方=( ).x平方+3xy-2y
-
x平方+xy= - 4,xy+y平方=5,则x平方+2xy+y平方=()
-
x平方-y平方=20 求((x+y)平方+4xy)((x+y)平方-4xy)
-
x平方-2xy-3y平方=0可变为(x+y)(x-3y)=0则xy+4y平方分之xy-2y平方的值
-
|x-2|+x的平方-xy+1/4y的平方=0,则x=?y=?
-
x平方(4x平方+4xy+y平方)-4x平方y平方
-
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
-
有这样一道题:求代数式(3x平方y+4x平方y平方-xy平方+x平方y-2x平方y平方+xy平方-4x平方y-2x平方y
-
计算(x-y)(x平方+xy+y平方)-(x+y)(x平方-xy+y平方)